An Action Research in EMU: Integrating Community Based Service-Learning Projects - Ruso, Nazenin (Eastern Mediterranean University (EMU), 2012)
ABSTRACT: For an educational institution to be defined as excellent, personal development of the students should be facilitated in a holistic manner and this is possible through building better bridges to the real world outside campus borders. It is important for teachers to grow both academic and productive citizens for the future. Eastern Mediterranean University‘s mission involves the commitment to create a stimulating intellectual environment that fosters values of respect, empathy, and ethical responsibility. The main problem is that the affective goals of higher education such as growing helpful and caring citizens are not emphasized as much as cognitive goals. The purpose of this study is to examine the contributions of community based service-learning (Cbsl) projects on university students mainly in affective domain of learning. This study consists of an action research project and is carried out in the mode of case study method attempting to explore a unique phenomenon (community based service-learning project) in Eastern Mediterranean University. 80 students from 3 different classes were involved in this study. Triangulation, which involves different methods to gather information, was preferred and the desired data were collected through pre-test, post-test, reflective papers and semi-structured interviews. Project participants found Cbsl project to be an empowering and worthwhile experience. The major findings of the study showed that Cbsl projects challenged students to examine, formulate and articulate their values as well as building several skills like collaboration and problem solving crucial for their personal, vocational and cognitive growth. As a result of the projects, not only cognitive growth of students‘ but affective and behavioral development embracing personal growth, found within the frame of higher education, are also nourished. Therefore, the effective findings derived from this study encourage school administrations to adopt Cbsl projects and accept them as a doctrinal part of education. Keywords: Community based service-learning project (Cbsl), affective domain, building skills, values development, cognitive growth.

ÖZ: Bir eğitim kurumunun mükemmel olarak tanımlanabilmesi için, öğrencilerin kişisel gelişimine de holistik bir tutum içerisinde olanak sağlanması gereklidir ve bunun mümkün olması ise kampüs sınırları dışında bulunan gerçek dünyayla daha iyi köprüler kurmakla bağlantılıdır. Öğretmenlerin gelecek için hem akademik hem de üretken vatandaşlar yetiştirmeleri çok önemlidir. Doğu Akdeniz Üniversitesi‘nin misyonu da stimule edici, entellektüelliği, saygıyı, empatiyi ve etik sorumlulukları güdücü bir ortam yaratmakla yükümlü olmayı içermektedir. Temel problem, yardımsever ve şefkatli vatandaş yetiştirme gibi yüksek eğitime ait olan duyuşsal amaçların, bilişsel gelişim kadar çok önemsenmemesidir. Bu çalışmanın amacı topluma dayalı hizmet öğrenimi projelerinin üniversite öğrencileri üzerinde başlıca duyuşsal öğrenim alanına olan katkılarını incelemektir. Bu çalışma eylem araştırması projesinden oluşmakta ve durum çalışması modunda Doğu Akdeniz Üniversitesi‘nde kendine özgü bir görüngüyü (topluma dayalı hizmet öğrenimi projeleri) ortaya çıkarmaya çalışmaktır. Çalışmanın örneklemini üç farklı sınıfta bulunan toplam 80 öğrenci oluşturmaktadır. Farklı veri toplama araçları içeren üçgenleme metodu tercih edilmiş ve istenen veriler ön test, son test, yansıtıcı yazılar ve yarı yapılandırılmış görüşmeler aracılığıyla toplanmıştır. Projeye katılan öğrenciler, Topluma Dayalı Hizmetten Öğrenim Projelerinin salahiyet verici ve zaman harcamaya değer bir deneyim olduğu kanısına varmışlardır. Çalışmanın temel bulguları gösteriyor ki topluma dayalı hizmetten öğrenim projeleri öğrencilerin değerlerini inceleyip, formüle edip açıkça belirtmesinin yanısıra, işbirliği ve problem çözme gibi onların kişisel, mesleki ve bilişsel gelişimine de önemli katkı sağlayan becerilerini de geliştirmektedir. Projeler neticesinde sadece bilişsel eğitim değil, yüksek eğitimin amaçları çerçevesinde olan kişisel gelişimi içeren, duyuşsal ve davranışsal gelişim de güdülmüştür. Bu çalışma neticesinde elde edilen etkili bulgular okul yönetimlerini topluma dayalı hizmetten öğrenim projelerini benimseme ve eğitimin kuramsal bir parçası haline getirmeyi teşvik etmektedir.
Doctor of Philosophy in Educational Sciences. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Education, Dept. of Educational Sciences, 2012. Supervisor: Prof. Dr. Mehmet Altınay.
Keywords: Educational Sciences; Affective Education; Community Based Service - Learning Project (Cbsl) - Affective Domain - Building Skills - Values Development - Cognitive Growth; Education, Humanistic - Eastern Mediterranean University - Cyprus, North